Ecology of ticks in a taxocenosis of snakes from the Serra do Mendanha, Rio de Janeiro, Brazil, with new host records - Jorge A. L. Pontes; Gilberto S. Gazêta; Davor Vrcibradic; Carlos F. D. Rocha (Zoologia (Curitiba), 2009)
We studied the ecology of ticks found in different species of a taxocenosis of snakes from the Serra do Mendanha, an area of Atlantic Rainforest located in the state of Rio de Janeiro, southeastern Brazil. Snakes were sampled monthly in the field during a period of 48 months. The specific identity of the hosts and their parasites, the number of parasites, and and snout-vent length and body mass of each host were recorded. A total of 25% of the species of snakes in the area were parasitized by ticks (larvae, nymphs and adult females) Amblyomma rotundatum Koch, 1844 was the predominant parasite species. The infestation parameters varied among the species of snakes sampled, with the highest prevalence of A. rotundatum being observed in the viperid Bothrops jararaca (Wied, 1824) (71.4%), followed by the colubrids Xenodon neuwiedii Günther, 1820 (33%), Chironius laevicollis (Wied, 1824) and Spilotes pullatus (Linnaeus, 1758) (both with 22%). The latter three species also showed the highest rates of infestation by A. rotundatum. The results of the present study suggest that a combination of skin shedding, habitat of the host, type of scale and pattern of scale distribution on the body of the host can influence the degree to which a given species is parasitized by ticks